Weathering words: a virtual reality study of environmental influence on reading dynamics - Rocabado, Francisco; Muntini, Laís; González Alonso, Jorge; Duñabeitia, Jon Andoni (Frontiers in Psychology, 2024)
Reading is an integral cognitive activity, influenced by both textual and external environmental factors, though the latter remains less explored. Using Virtual Reality (VR) technology, we investigated how visual contrast and simulated weather conditions affect reading dynamics. Experiment 1 revealed that high visual contrast, especially in sunny conditions, significantly boosted single-word recognition speed, showing the significant influence of environmental visual conditions through a lexical decision task. Experiment 2, however, displayed a different dynamic on a sentence reading task: while visual contrast had minimal impact on reading, sunny weather led to faster reading times, and rainy scenarios resulted in increased eye fixations. These results suggest that environmental factors can significantly affect reading behavior. The current study collaborates with the characterization of the key features influencing reading in daily life contexts. It can inform the design of ergonomic reading materials, particularly in outdoor and VR environments. The integration of stimuli within a controlled environment and its manipulation increases ecological validity in the reading research and highlights the potential of VR as a tool for in-depth cognitive research.